Linking Learning Contexts: The Relationship between Students’ Civic and Political Experiences and Their Self-Regulation in School - Malafaia, Carla; Teixeira, Pedro M.; Neves, Tiago; Menezes, Isabel (Frontiers in Psychology, 2016)
This paper considers the relationship between self-regulation strategies and youth civic and political experiences, assuming that out-of-school learning can foster metacognition. The study is based on a sample of 732 Portuguese students from grades 8 and 11. Results show that the quality of civic and political participation experiences, together with academic self-efficacy, are significant predictors of young people’s self-regulation, particularly regarding cognitive and metacognitive strategies (elaboration and critical thinking). Such effects surpass even the weight of family cultural and school variables, such as the sense of school belonging. There-fore, we argue that the pedagogical value of non-formal civic and political experiences is re-lated to learning in formal pedagogical contexts. This is because civic and political participa-tion with high developmental quality can stimulate higher-order cognitive engagement and, thus, contribute to the development of learning strategies that promote academic success.